Sum of the reciprocals of the binomial coefficients (Q685302): Difference between revisions

From MaRDI portal
Added link to MaRDI item.
RedirectionBot (talk | contribs)
Removed claim: author (P16): Item:Q590359
Property / author
 
Property / author: Balasubramanian Sury / rank
Normal rank
 

Revision as of 15:37, 19 February 2024

scientific article
Language Label Description Also known as
English
Sum of the reciprocals of the binomial coefficients
scientific article

    Statements

    Sum of the reciprocals of the binomial coefficients (English)
    0 references
    17 October 1993
    0 references
    Let \(S_ n=\sum^ n_{k=0}{1 \over {n \choose k}}\). It is shown that \(S_ n\) satisfies the recurrence \(S_ n={n+1 \over 2n}S_{n-1}+1\). The proof can be simplified by observing that \[ n!S_ n=\sum^ n_{k=0}k!(n-k)!=n!+\sum^{n-1}_{k=0}k!(n-k-1)!(n+1-k-1) =n!+(n+ 1)(n-1)!S_{n-1}-(n!S_ n-n!). \]
    0 references
    0 references
    reciprocals
    0 references
    binomial coefficients
    0 references

    Identifiers